2000
DOI: 10.1161/01.atv.20.10.2220
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fluid Flow on Smooth Muscle Cells in a 3-Dimensional Collagen Gel Model

Abstract: Abstract-A 3D collagen gel model was developed to simulate interstitial fluid flow and to assess the importance of this flow on the biochemical production rates of vascular smooth muscle cells (SMCs). Rat aortic SMCs were suspended in type I collagen, and the gel was supported by nylon fibers that allowed a 9-cm length of the SMC-gel model to withstand 90 cm H 2 O differential pressure over a 6-hour period without significant compaction. Up to 1 dyne/cm 2 shear stress on the suspended SMCs could be induced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
117
1
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(124 citation statements)
references
References 19 publications
3
117
1
2
Order By: Relevance
“…Transvascular flow across the arterial wall provides nutrient transport to the metabolically active cells there, and seemingly has a crucial role in maintaining arterial smooth muscle tone [21][22][23]. In cartilage, where lymphatics are absent and intercellular distances are large, interstitial fluid flow is driven by mechanical loading and is necessary for nutrient transport and cell-cell communication when diffusion is inadequate [24][25][26].…”
Section: Box 1 Darcy's Lawmentioning
confidence: 99%
“…Transvascular flow across the arterial wall provides nutrient transport to the metabolically active cells there, and seemingly has a crucial role in maintaining arterial smooth muscle tone [21][22][23]. In cartilage, where lymphatics are absent and intercellular distances are large, interstitial fluid flow is driven by mechanical loading and is necessary for nutrient transport and cell-cell communication when diffusion is inadequate [24][25][26].…”
Section: Box 1 Darcy's Lawmentioning
confidence: 99%
“…Shear stress is also considered as an important parameter for in vivo systems. Wang and Tarbell (2000) found by experiments for smooth muscle cells that with increasing shear stress the production of prostaglandins increased. The results of Wang and Tarbell (2000) indicate that the blood flow rate plays a role in the signal communication system from the blood vessels to the smooth muscle cells.…”
Section: Introductionmentioning
confidence: 98%
“…However, if we realize that the pressure drop caused by fluid-wall interaction in a structure is proportional to permeability of the structure, then it is also an option to link the shear stress to permeability constants. Wang and Tarbell (2000) use the permeability constant from Darcy's law to derive the average shear stress from experiments on a collagen gel. The permeability constant was determined using the viscosity of the perfusing medium, the measured volumetric flow rate, the cross-sectional area and the imposed pressure drop over the length of the reactor.…”
Section: Introductionmentioning
confidence: 99%
“…This autocrine signaling mechanism, termed autologous chemotaxis, arises in a flow field where convection distributes autocrine chemokine factors creating a transcellular chemokine gradient, which in turn provides a chemotactic signal. For CCL21 at physiologically relevant flow velocities, flow increases the concentration of ligand at the downstream side of the cell, providing a positive downstream chemotactic signal (14).The transwell assay used by Shields et al to develop the autologous chemotaxis model and other similar in vitro assays have provided valuable insight into the metastatic process and tumor cell migration by allowing the systematic study of isolated stimuli on tumor cells (9,10,(15)(16)(17)(18)(19). However, recent work has demonstrated that focal adhesion (FA) formation and regulation are a function of dimensionality of cell culture (20), and previous work has demonstrated FA formation is important in regulating endothelial cell (EC) response to laminar shear stress (21).…”
mentioning
confidence: 99%